2021
DOI: 10.1186/s12891-021-04425-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of missed fractures of hand and forearm in whole-body CT in a blinded reassessment

Abstract: Background We examined the visibility of fractures of hand and forearm in whole-body CT and its influence on delayed diagnosis. This study is based on a prior study on delayed diagnosis of fractures of hand and forearm in patients with suspected polytrauma. Methods Two blinded radiologists examined CT-scans of patients with fractures of hand or forearm that were diagnosed later than 24 h after admission and control cases with unremarkable imaging o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…After repeated examination, secondary imaging, and reporting, 20.3% of the injuries remained unreported. In literature, the frequencies of missed wrist/hand fractures differ between 4.1 and 32.9% [ 10 , 12 , 14 ]. Missed injuries have been shown to be more likely in intubated and severely injured patients [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After repeated examination, secondary imaging, and reporting, 20.3% of the injuries remained unreported. In literature, the frequencies of missed wrist/hand fractures differ between 4.1 and 32.9% [ 10 , 12 , 14 ]. Missed injuries have been shown to be more likely in intubated and severely injured patients [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Missed injuries have been shown to be more likely in intubated and severely injured patients [ 24 , 25 ]. Previous data also suggests that on-call duty predisposes for missed fractures and other injuries [ 14 , 26 ]. Nevertheless, reasons for underreporting were not identified by this current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Scandinavian study has assessed the total number of correctly diagnosed and missed fractures per hour of a day and they observed that the rate of missed fractures surpassed the number of correctly diagnosed fractures between 5 p.m. and 7 a.m., i. e., during the night shifts [30]. Other studies have also reported that on-call duty is a factor contributing to the missing of fractures and other injuries [31,32]. Other factors include a level of experience on the part of the reader (most on-call duties are performed by radiologists in training) and image interpretation under stressful conditions in the emergency room [10], lack of clinical information, absence of previous imaging studies, suboptimal reading room atmosphere, multitasking and increased workload [10] all factors that are often typical of on-call duties and night and weekend shifts.…”
Section: The Human Factormentioning
confidence: 99%